Acetylene oligomerization on the surface of TiO2: a step forward in the in situ synthesis of nanostructured carbonaceous structures on the surface of photoactive oxides - Sagar Jain (Journal of Materials Chemistry A, 2014)
The interaction of acetylene with TiO2 (Evonik P25) was studied as a function of gas pressure and contact time by in situ vibrational (infrared and Raman) and electronic (UV-vis) spectroscopy and by gas chromatography-mass spectrometry analysis (GC-MS) of the reaction products. At low pressure the reaction proceeds through surface adsorption of acetylene and cyclotrimerization to benzene. At higher pressure (P > 100 mbar) the adsorption step is followed by the progressive formation of more complex oligomerization products containing an increasing number of conjugated double bonds. The final products obtained after mild heating at 373 K in acetylene excess absorb in the visible spectral region and confer to the system a strong blue color. These colored species are stable for many days in pure oxygen or air and cannot be extracted with common solvents, appearing strongly anchored to the TiO2 surface. The formation of saturated –CH3 and –CH2 groups during the oligomerization process and the spectroscopic and GC-MS results show that the colored species consist of polycyclic aromatic hydrocarbons containing a considerable number of condensed rings. Following these results, the controlled oligomerization of acetylene can represent a route for direct production of graphene-like species tightly anchored to the TiO2 surface, i.e. of composite materials of potential interest in photocatalysis or photovoltaic applications.